Link between distal sensory polyneuropathy, insulin-like growth factor-I and bone mineral density in elderly diabetics - Amer, Moatassem S.; Rahman, Tomader T. Abdel; Adly, Nermien N.; Hassanin, Hany I. (International Journal of Research in Medical Sciences, 2017)
Background: The association between Distal Sensory Polyneuropathy (DSP) and systemic osteopenia was studied before in type 1 Diabetes Mellitus (DM), however, is not all clear, with scanty researches in type 2 DM. In addition, Insulin-like Growth Factor-I (IGF-1) could be the most important mediator of bone growth, and an important neurotrophic factor for peripheral sensory neurons. Therefore, the aim of this study was to study the association between bone mineral density (BMD) and DSP, in elderly patients with type 2 DM, and the link between IGF-1 and both BMD and DSP. Methods: Eighty eight elderly patients, aged ≥60 years, were involved in this case (43 diabetics with DSP and 17 diabetics without DSP) - control (28 non diabetics) study. BMD and IGF-1 were measured. Results: There was no significant difference between cases and controls regarding T score of either lumbar spine or femoral neck or IGF-1 (P = 0.83, 0.96 and 0.17 consecutively). DM without DSP had higher IGF-1 than both DM with DSP& the control group (P = 0.011 and 0.010 consecutively). IGF-1 was a significant predictor of T score of both femoral neck and lumbar spine, only in the control group (P = 0.008 and <0.001 consecutively) (OR=1.44 and 2.4 consecutively) (CI=1.1-1.9 and 1.9-3.1 consecutively). Neither DSP nor IGF-1 was (were) a significant predictor of BMD in diabetics. Conclusion: There was no association between type 2 DM and BMD. IGF-1 was higher in diabetics without DSP than those with DSP or the control group. IGF-1 was a positive predictor of BMD only in the control group.